PENGEMBANGAN MEDIA MIND MAPPING BERBANTUAN LIFT THE FLAP PADA MATERI RANTAI MAKANAN UNTUK SISWA KELAS V SD NEGERI 142 PALEMBANG - Silpa Kholonisa; Sukardi; Aldora Pratama (STKIP Subang, 2023)
ABSTRACT This development research aims to: how is the development of lift the flap assisted mind mapping media on food chain material for fifth grade students at SD Negeri 142 Palembang which is valid and practical. The method used in this study is the R&D (Research and Development) method with the ADDIE model. The development research process was carried out in several stages of the ADDIE model, namely: Analyze, Design, Development, Implementation, and Evaluation. The analyze phase is carried out by analyzing field observation data in the form of needs analysis and material analysis. The design stage is to design learning media. The development stage includes the creation of learning media, which will be validated by material experts and media experts as well as 2 trials consisting of: 1. One to one 2. Small group. The implementation stage is a trial run to all students which is carried out on 27 students. The evaluation stage is evaluating the feasibility and practicality of the media. Based on the results of the study, it was shown that the assessment by media experts obtained a score of 77.33% in the